Sri Lanka Development Update, February 2019 : Demographic Change in Sri Lanka - World Bank (World Bank, Washington, DC, 2019)
Sri Lanka is facing a challenging macroeconomic landscape. The post-conflict high growth momentum has decelerated. A volatile global environment and structurally weak competitiveness continue to weaken growth and external sector performance. High interest costs mask limited fiscal improvement. While outlook remains stable conditional on political stability and reform implementation, the balance of risks is downward tilted. The country is vulnerable to global financial market conditions due to large refinancing requirements. Although some important reforms were carried out, the process has slowed down due to a challenging political environment.